Pd-Shaped Nanoparticles Modified by Gold ad-Atoms: Effects on Surface Structure and Activity Toward Glucose Electrooxidation - Rafaïdeen, Thibault; Baranton, Stève; Coutanceau, Christophe (Frontiers in Chemistry, 2019)
Palladium nanoparticles (Pd-NPs) with controlled distributions of sizes and shapes (nanospheres - Pd-NS-, nanocubes -Pd-NC-, and nanooctahedrons -Pd-NO-) are synthesized by wet chemistry methods and characterized by TEM/HRTEM. The surfaces of Pd-NPs are modified by spontaneous adsorption of gold and characterized by cyclic voltammetry in acidic medium. It is shown that the modification of Pd-NPs by dipping in HAuCl4 solutions of different concentrations allows controlling the surface coverage by gold. It is also shown that the modification of Pd-NPs surfaces involves first the formation of PdAu surface alloys. For higher coverages, both PdAu surface alloys and pure Au structures are formed. The activity towards the glucose electrooxidation reaction is determined by linear scan voltammetry (LSV). Higher activity is observed on pure Pd-NC presenting extended (100) surfaces than on Pd-NO with mainly (111) surface orientation and on Pd-NS without preferential surface orientation, both these latter Pd-NPs displaying almost the same activity. The modification of the surface by spontaneous adsorption of gold greatly improves the activity of all Pd-NPs. However, Au-modified Pd-NC materials remain the most active catalysts. PdAu surface alloys seem to be involved in the improvement of the catalytic activity at low potentials, although the role of pure gold structures on Pd-NPs towards the enhancement of the catalytic activity cannot be excluded for high gold coverage. The study allows a better understanding of the material structure/electrocatalytic behavior relationship.